(untitled) (Research, Society and Development, 2020)
The Geographical Indication (GI) is the recognition used to indicate the origin of a product or service in a given region or locality. Protection for products or services, with specific characteristics attributable to the geographical environment, has been growing around the world and GI, constituted as an instrument of intellectual property, are becoming increasingly important for regional development and international trade. In this perspective, this article carried out a bibliometric study in order to know the scenario and research trends on the theme of GI at an international level, by surveying the scientific productions contained in the Scopus and Web of Science research bases, in the period between 2010 to 2019. For that, the keywords “Geographical Indication” or “Indication of Provenance” or “Indication of origin” were used as an article search method, along with the Article title, Abstract and Keywords descriptors of the databases consulted. After refinement and adequacy of the identified works, 374 publications were analyzed. The results of this study point to Italy, France and Brazil with the highest occurrences of publications. Biological and Agricultural Sciences (45%), Social Sciences (26%), Business, Management and Accounting (12%), Environmental Science (9%) and Economics, Econometrics and Finance (8%) contemplate the areas of concentration of studies on IG. It was identified as clusters of scientific production content networks related to GI and its legal aspects, GI and differentiation, Governance and rural development.